Bullying nas escolas: análise das medidas existentes no PPP de duas escolas públicas de Manaus - Castro, Alynne Cardoso de (Brasil, 2025)
This article analyzes the Pedagogical Political Projects (PPPs) of two public schools in the city of Manaus, with the aim of investigating which preventive actions against bullying in schools are provided for in the documents. These documents exhibit the actions and principles followed by the institutions, and therefore, the analysis allows us to understand how this violence is addressed in schools in the current social context. The research was developed using a qualitative approach for document analysis, with the documents being primary sources produced by the public schools and approved by the State Department of Education. The results show that the PPP of School A presents principles and guidelines aimed at respecting differences and emphasizes the need to promote actions against bullying at school, highlighting the responsibility of teachers and pedagogues to act preventively. The participation of everyone ensures the full achievement of the goals set out in the Action Plan. The PPP of School B indicates principles focused on youth protagonism, forming students not only intellectually, but also socially conscious young people. No actions specifically aimed at bullying were presented. The school presents actions in the general context of coexistence and respect for differences.